2011
DOI: 10.2165/11539680-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Human Intravenous and Oral Pharmacokinetics of 21 Diverse Compounds Using Physiologically Based Pharmacokinetic Modelling

Abstract: The results from this evaluation demonstrate the utility of PBPK methodology for the prediction of human pharmacokinetics. This methodology can be applied at different stages to enhance the understanding of the compounds in a particular chemical series, guide experiments, aid candidate selection and inform clinical trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 37 publications
2
93
1
Order By: Relevance
“…Typically, generic PBPK models assume flow-limited distribution and well stirred tissue kinetics. Successful predictions using these PBPK models have been made for lipophilic compounds whose absorption and distribution are governed by passive processes (Jones et al, 2006(Jones et al, , 2011Rostami-Hodjegan and Tucker, 2007). However, these models would not be expected to provide reasonable predictions for compounds that are actively transported.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, generic PBPK models assume flow-limited distribution and well stirred tissue kinetics. Successful predictions using these PBPK models have been made for lipophilic compounds whose absorption and distribution are governed by passive processes (Jones et al, 2006(Jones et al, , 2011Rostami-Hodjegan and Tucker, 2007). However, these models would not be expected to provide reasonable predictions for compounds that are actively transported.…”
Section: Introductionmentioning
confidence: 99%
“…These models use physiologically relevant parameters describing absorption, distribution, metabolism and excretion (ADME) to predict the overall pharmacokinetic (PK) profile of a compound. The use of PBPK models has increased significantly in recent years, and reports of successful retrospective application with large industrial data sets are forthcoming [5][6][7]. An important aspect of PBPK modeling for compounds cleared primarily by the liver is the application of IVIVE methods to predict in vivo clearance from in vitro metabolic data.…”
Section: Introductionmentioning
confidence: 99%
“…More complex disposition models could be utilized. A recent study found that physiologically based pharmacokinetic models (PBPK) were able to accurately predict the multiphasic shape of the pharmacokinetic profiles for many of the compounds tested (8). Since it is the shape of the unit input function that is most important (rather than the magnitude on the absorption axis), a PBPK simulated solution unit impulse might offer advantages over one derived from a one-compartment model when a more complex disposition is anticipated.…”
Section: Discussionmentioning
confidence: 99%